Revealing phosphorylation regulatory networks during embryogenesis of honey bee worker and drone (Apis mellifera) - Ma, Beibei; Ma, Chuan; Li, Jianke; Fang, Yu (Frontiers in Cell and Developmental Biology, 2022)
Protein phosphorylation is known to regulate a comprehensive scenario of critical cellular processes. However, phosphorylation-mediated regulatory networks in honey bee embryogenesis are mainly unknown. We identified 6342 phosphosites from 2438 phosphoproteins and predicted 168 kinases in the honey bee embryo. Generally, the worker and drone develop similar phosphoproteome architectures and major phosphorylation events during embryogenesis. In 24 h embryos, protein kinases A play vital roles in regulating cell proliferation and blastoderm formation. At 48-72 h, kinase subfamily dual-specificity tyrosine-regulated kinase, cyclin-dependent kinase (CDK), and induced pathways related to protein synthesis and morphogenesis suggest the centrality to enhance the germ layer development, organogenesis, and dorsal closure. Notably, workers and drones formulated distinct phosphoproteome signatures. For 24 h embryos, the highly phosphorylated serine/threonine-protein kinase minibrain, microtubule-associated serine/threonine-protein kinase 2 (MAST2), and phosphorylation of mitogen-activated protein kinase 3 (MAPK3) at Thr564 in workers, are likely to regulate the late onset of cell proliferation; in contrast, drone embryos enhanced the expression of CDK12, MAPK3, and MAST2 to promote the massive synthesis of proteins and cytoskeleton. In 48 h, the induced serine/threonine-protein kinase and CDK12 in worker embryos signify their roles in the construction of embryonic tissues and organs; however, the highly activated kinases CDK1, raf homolog serine/threonine-protein kinase, and MAST2 in drone embryos may drive the large-scale establishment of tissues and organs. In 72 h, the activated pathways and kinases associated with cell growth and tissue differentiation in worker embryos may promote the configuration of rudimentary organs. However, kinases implicated in cytoskeleton organization in drone embryos may drive the blastokinesis and dorsal closure. Our hitherto most comprehensive phosphoproteome offers a valuable resource for signaling research on phosphorylation dynamics in honey bee embryos.